2015
DOI: 10.1155/2015/912942
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Water Treatment Residual Nanoparticles as a Sorbent for Arsenic Removal

Abstract: A novel sorbent, water treatment residual nanoparticles (nWTR), was synthesized and used to remove As(V) from water solutions. The kinetics and equilibrium of As(V) adsorption by nWTR were evaluated. The kinetic data for nWTR at 3 different pH values indicate that As(V) sorption is biphasic, is favored at low pH values, and followed the power function and first-order kinetics models fit. The results of the batch adsorption study showed that nWTR was effective in As(V) removal and its removal capability was 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…Our research findings suggested that application of nWTR could be considered as best management practice to retain and immobilize excess Hg and could provide long-term sorption stability. This is in accordance with the results of Elkhatib et al (2015c), who reported the high capability of nWTR to immobilize As.…”
Section: % Wtrsupporting
confidence: 93%
See 4 more Smart Citations
“…Our research findings suggested that application of nWTR could be considered as best management practice to retain and immobilize excess Hg and could provide long-term sorption stability. This is in accordance with the results of Elkhatib et al (2015c), who reported the high capability of nWTR to immobilize As.…”
Section: % Wtrsupporting
confidence: 93%
“…This is in accordance with the results of Elkhatib et al . (), who reported the high capability of nWTR to immobilize As.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations